Clopidogrel Versus Aspirin as Chronic Maintenance Antiplatelet Monotherapy in Patients After Percutaneous Coronary Intervention With Chronic Kidney Disease: A Post Hoc Analysis of the HOST‐EXAM Trial - Jeehoon Kang; Sang‐Hyeon Park; Kyung Woo Park; Bon‐Kwon Koo; Huijin Lee; Minju Han; Doyeon Hwang; Han‐Mo Yang; In‐Ho Chae; Won‐Yong Shin; Ju Hyeon Oh; Yong Hoon Kim; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Clopidogrel monotherapy improved clinical outcomes compared with aspirin monotherapy during a chronic maintenance period in patients who underwent coronary stenting in the HOST‐EXAM (Harmonizing Optimal Strategy for Treatment of Coronary Artery Stenosis–Extended Antiplatelet Monotherapy) trial. However, it is uncertain whether the beneficial effect of clopidogrel over aspirin is different according to the renal function. Methods and Results We conducted a post hoc analysis of the HOST‐EXAM trial. Chronic kidney disease (CKD) was defined as baseline estimated glomerular filtration rate <60 mL/min per 1.73 m2. The primary end point was a composite of all‐cause death, nonfatal myocardial infarction, stroke, readmission due to acute coronary syndrome, and Bleeding Academic Research Consortium bleeding type ≥3, during the 2‐year follow up. Among the 5438 patients enrolled in the HOST‐EXAM trial, 4844 patients (mean age, 63.3±10.6 years; 74.9% men) with a baseline creatinine value were analyzed in this study. A total of 508 (10.5%) patients had CKD, who were at higher risk of the primary end point compared with those without CKD (hazard ratio [HR], 2.01 [95% CI, 1.51–2.67]). Clopidogrel monotherapy was associated with a lower rate of the primary end point in both patients with CKD (HR, 0.74 [95% CI, 0.44–1.25]) and patients without CKD (HR, 0.71 [95% CI, 0.56–0.91]). No significant interaction was observed between the treatment effect and CKD status (P for interaction=0.889). Conclusions During the chronic maintenance period after coronary stenting, the risk of thrombotic and bleeding events was significantly higher in patients with CKD compared with those without CKD. There was no statistical difference in the treatment effect of clopidogrel monotherapy in those with versus without CKD.